Diversity and Evolution of Disease Resistance Genes in Barley (Hordeum vulgare L.). (January 2016) - Andersen, Ethan J.; Ali, Shaukat; Reese, R. Neil; Yen, Yang; Neupane, Surendra; Nepal, Madhav P.
Plant disease resistance genes (R-genes) play a critical role in the defense response to pathogens. Barley is one of the most important cereal crops, having a genome recently made available, for which the diversity and evolution of R-genes are not well understood. The main objectives of this research were to conduct a genome-wide identification of barley Coiled-coil, Nucleotide-binding site, Leucine-rich repeat (CNL) genes and elucidate their evolutionary history. We employed a Hidden Markov Model using 52 Arabidopsis thaliana CNL reference sequences and analyzed for phylogenetic relationships, structural variation, and gene clustering. We identified 175 barley CNL genes nested into three clades, showing (a) evidence of an expansion of the CNL-C clade, primarily due to tandem duplications; (b) very few members of clade CNL-A and CNL-B; and (c) a complete absence of clade CNL-D. Our results also showed that several of the previously identified mildew locus A ( MLA ) genes may be allelic variants of two barley CNL genes, MLOC_66581 and MLOC_10425, which respond to powdery mildew. Approximately 23% of the barley CNL genes formed 15 gene clusters located in the extra-pericentromeric regions on six of the seven chromosomes; more than half of the clustered genes were located on chromosomes 1H and 7H. Higher average numbers of exons and multiple splice variants in barley relative to those in Arabidopsis and rice may have contributed to a diversification of the CNL-C members. These results will help us understand the evolution of R-genes with potential implications for developing durable resistance in barley cultivars.